Traditional maize farming management practices and family involvement of smallholder farmers in Aurora, Zamboanga del Sur, Philippines - Villaver, J. P.; Alivio, E. M.; Hajim, J. A.; Laylay, R. J. H. (International Journal of Agricultural Technology, 2021)
The smallholder farmers’ existing farming practices in Aurora, Zamboanga del Sur was determined. The survey revealed that most of the farmers adopted an integrated farming system (69.8%) and preferred native corn (96.2%) for their consumption. They till a loamy soil (73.6%) with a rolling topography (58.5%) at an area of less than 1 hectare (67.9%). The soil is prepared in a minimum tillage system (56.6%) using an animal-drawn plow (83.9%). Most of them applied herbicide (77.2%) before furrowing. Farmers used inorganic fertilizers (98.1%) like ammonium sulfate, urea, complete fertilizer, and ammonium phosphate. The farmers encountered problems like lack of capital (98.1%), adverse environmental conditions (86.8%), low crop production (69.8%), invasion of pests and diseases (58.5%), and cheap market price (56.6%). Their farms are situated less than 500 meters to the barangay road (75.5%) and more than 1 km to the national road (90.6%). They transported their products manually or with the aid of a motorcycle (96.40%). As to family participation, the father ranked number 1 as the main actor in farming. A mother ranked as the second performer in farming activities in support of the father. A son (rank 3) and daughter (rank 4) were seldom involved in farming activities. This investigation found out that the government should consider corn production training with access to capital or funding institutions to achieve a successful production. Family involvement in farming is also encouraged to strengthen the common goal of attaining food sufficiency. An in-depth understanding of the needs and traditional farming practices would arrive at a better design intervention of the policymakers to improve the existing practices, increase production and income of the smallholder farmers in Aurora, Zamboanga del Sur, Philippines